Qualitative Analysis of Anti-protozoan Drug Tinidazole by Vibrational and UV-Visible Spectroscopy - Gunasekaran, S.; Anita, B. (Asian Journal of Chemistry, 2010)
Modern spectroscopic techniques serve as indispensable tools for the qualitative analysis of pharmaceutical products. In this work, a qualitative analysis of a commonly used anti-protozoan drug, tinidazole has been carried out using FTIR, FT-Raman and UV-visible spectroscopic techniques. A satisfactory vibrational band assignment of the drug has been made based on the position, shape and relative intensity of the recorded spectra, in correlation with bands assigned in structurally related molecules. The quality of the drug has been studied by storing it in different conditions and analyzing their spectra by internal standard ratio method. The stress degradation behaviour of the drug has been studied by employing FTIR and UV-Visible spectral techniques.